Multiorgan procurement is associated with a survival benefit after heart transplantation. Issue 8 (25th May 2020) - Magruder, Jonathan Trent; Suzuki, Yoshikazu; Sperry, Alexandra; Vasquez, Charles R.; Smood, Benjamin; Grimm, Joshua C.; Atluri, Pavan; Bermudez, Christian; Acker, Michael A.; Wald, Joyce W.; Cantu, Edward; Cevasco, Marisa
Abstract: We assessed the impact of donor multiorgan procurement on survival following orthotopic heart transplantation (OHT). From the UNOS STAR database, we included all adult (≥18 Y) heart transplants (OHT) performed since 2000 and used donor IDs to determine how many other organs were procured from the same donor as the recipient's heart allograft (regardless of recipient). The Kaplan‐Meier survival functions and risk‐adjusted Cox proportional hazards regression models were computed to assess the association of multiorgan procurement with post–heart transplantation mortality. We included 40 336 OHT patients. Including the heart, the median number of donor organs procured was 3 (IQR, 3‐4). Heart donors underwent liver procurement in 89.7%; kidney(s) in 98.1% (single 95%, bilateral 5%); lung(s) in 38.0% (single 28%, bilateral 72%); pancreas in 10.4%; and intestine in 1.6%. Following risk adjustment across 16 recipient‐ and donor‐specific variables, an increasing number of organs procured were independently associated with reduced post‐OHT mortality (HR 0.98, 95% CI 0.96‐0.99, P  = .025). Though no significant associations were found examining specific organ types, double lung procurement trended toward a protective effect (HR 0.96, 0.92‐1.01, P  = .086), with counts of non‐lung organs procured still bordering on significance (HR 0.97, 95% CI 0.95‐1.00, P  = .067). These results likely reflect improved multiorgan donor quality.